Educação Física e pedagogia histórico-crítica: aproximações históricas e apropriações teóricas - Andrade, Leonardo Carlos de (2021)
The present work had the general objective to analyze how Physical Education has approached the historical-critical pedagogy and what the foundations of this pedagogical theory have been appropriated by reference works in the field. In this way, 1) We map and analyze the existing production between Physical Education and historical-critical pedagogy in the period between 1996-2019; 2) We identified the main theoretical productions that are references in this theme, by the criterion of citation between pairs; 3) We identified which fundamentals of historical critical pedagogy were appropriated by the main references of Physical Education on the subject. Therefore, we captured through bibliographical research the process of propositional development of the approximations of Physical Education with the historical critical pedagogy and the identification of the philosophical, pedagogical and psychological foundations that have been appropriated. In chapter 1, we historically contextualize the approximations between historical-critical pedagogy and Physical Education, from the renovating movement to contemporaneity. For that, we traced the following path: 1º) Emergence and characterization of the historical-critical pedagogy; 2º) First approximations between Physical Education and historical-critical pedagogy, in the renovating movement; 3rd) Timeline about the main events on the topic; 4th) Presentation of reference works in the debate on Physical Education and historical-critical pedagogy between 1996 and 2019. In Chapter 2, we present the philosophical foundations that were identified in the 9 reference works on the theme: I) Work and Human Formation; II) Human Gender and Educational Work; III) Alienation and Class Struggle; IV) Emancipation and Freedom. In Chapter 3, we present the pedagogical and psychological foundations that were identified in the 9 works, condensed in the debate on: I) School Education; II) School Knowledge; III) Didactic Bases and Propositions. Through the analysis of the appropriate categories by the 9 works of Physical Education, we capture a trend in the incorporation of the fundamentals of historical-critical pedagogy, primarily by the classics of this pedagogical theory, Marxism and historical-cultural psychology, showing an effort by the field to develop its appropriations very consistently.